Language diversity in mathematics education in the Nordic countries 2008–2018 - Meaney, Tamsin; Eskeland Rangnes, Toril (NOMAD Nordic Studies in Mathematics Education, 2018)
In 2008, the Nordic Studies in Mathematics Education (Nomad) journal published a thematic issue on Bringing focus to mathematics education in multicultural and multilingual settings. It had four articles with contributors from Australia, Sweden, Denmark and New Zealand ...